Eating One's Own A Conversation with David Armitage. - Burton, Howard (Ideas Roadshow Conversations Ser., 2020)
This book is based on an in-depth filmed conversation between Howard Burton and intellectual historian David Armitage, the Lloyd C. Blanfein Professor of History at Harvard University. This conversation covers David Armitage's research on the history of ideas of civil war from Ancient Rome to the present. A salient feature of Armitage's work is a strong focus on etymology as it relates to our understanding of how people interpreted (or misinterpreted) and perceived events in history which results in a fascinating exploration of how our understanding of various concepts has been prejudiced by p.